Cultivo in vitro e análise qualitativa da fisalina D em Physalis angulata L. - Pereira, Danilo Marcelo Santos (2011)
The camapu "(Physalis angulata L.) belongs to the Solanaceae family is recognized for its medicinal importance, due to the production of vitaesteróides with antineoplastic action (physalins). Tissue culture has been considered a promising tool for propagation of medicinal species, contributing to obtaining a higher content of bioactive compounds in these plants. This study aimed to develop protocols for the establishment of Physalis angulata environment in vitro by evaluating the effect of different types of culture media and growth regulators on organogenesis, rooting and callus formation, qualitatively assessing the presence of physalins D in leaves, roots and callus. For germination in vitro were used seeds collected from plants cultivated in Horto, Universidade Estadual de Feira de Santana (UEFS). The plants obtained were used for in vitro establishment of primary cultures on MS medium MS/2 and WPM. Once established, the nodal segments were transferred to medium Wood Plant Medium (WPM), identified as the best culture medium for Physalis angulata, supplemented with different concentrations of auxins and cytokinins. Plants from the previous experiment were rooted on WPM medium with different concentrations of IBA and subsequently acclimatized in a greenhouse. We evaluated the effect of different concentrations of plant growth regulators on callus induction from leaf explants and internode. We evaluated the presence of physalins D in different plant parts and callus. It was found that the species Physalis angulata features easy germination in different media tested, and that the use of "pulses" of BAP encourages more shoots in vitro multiplication. This species has great ease of rooting, even in the absence of growth regulators. Is possible obtain friable callus of Physalis angulata. Was confirmed the presence of physalins in vitro cultivated material. The results will provide reference for protocols multiplication of this species, supporting the improvement works aimed at obtaining plants with increased content and allow physalins future biotechnological approaches for production of these compounds in vitro.